DEVELOPMENT OF FUSARIUM DISEASE CONTROL TECHNOLOGY WITH BIOLOGICAL AGENT IN MAS CULTIVAR BANANA IN LAND INFECTED - Anis Shofiyani; Gayuh Prasetyo Budi (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2014)
Based on the data of General Director of Production and Horticulture, the damage of plantation areas in banana plantation centers in Indonesia always increases in years, this is due to Fusarium attack caused by fungus Fusarium oxisphorum and causing damage of 30- 70 % banana plantation areas.The aim of this empirically for due to biological control technology Fusarium wilt effective and environmentally friendly to the infected area in District Baturaden, Banyumas through soil solarization treatments and utilization of biological agents..The Research was conducted at the wilt disease endemic Fusarium land located in the village Pamijen, District Baturraden, Banyumas. The research design was a Split Plot Design consisting of 2 treatments, the main plot treatments is soil solarization, whereas treatment subplot is the type and dose of biological agents antagonist. The results showed that the treatment given soil solarization proved to increase the temperature of the surface of the soil up to 8.8 ° C compared with without solarization and reduces demand Fussarium population at ground level up to 53.61%, whereas without solarization Fussarium population decline by 22, 33%. Provision of biological agents Trichoderma, Gliocladium and P. Fluoroscens during the study proved to provide inhibition of the development of Fussarium on seedling disease, indicated by the appearance of symptoms of the disease until the end of the study. This is possible due to the formation of phenolic compounds such as tannins, saponins and glicosida and colonization between biological agents with the root system of plants in which the contact between pathogen inhibition with banana plant seedlings root system so that it protects the roots of the disease-causing pathogen infection Fussarium wilt. Treatment of biological agents proved capable of providing better vegetative growth when compared to the untreated biological agents (control) in which had significant effect on the number of root parameters, but had no significant effect on plant height parameter, number of leave’s, and stem’s diameter. However, the provision of Trichoderma 100 g / planting hole showed the best results in almost all plant vegetative growth parameters at the end of the reseach. Key word: solarize, biological agents, banana plants, infected with Fusarium land